Implementing a secure academic grid system - A Malaysian case - Sajat, Mohd Samsu; Hassan, Suhaidi; Ahmad, Adi Affandi; Daud, Ali Yusny; Ahmad, Amran (2012)
Computational grids have become very popular in the recent times due to their capabilities and flexibility in handling large computationally intensive jobs.When it comes to the implementation of practical grid systems,security plays a major role due to the confidentiality of the information handled and the nature of the resources employed.Also due to the complex nature of the grid operations, grid systems face unique security threats compared to other distributed systems.This paper describes how to implement a secure grid system with special emphasis on the steps to be followed in obtaining, implementing and testing PKI certificates.